PENINGKATAN KETERAMPILAN MENULIS TEKS LAPORAN OBSERVASI MELALUI PENGAMATAN KEMASAN BEKAS MINUMAN PADA SISWA KELAS X IPA 5 SMA NEGERI 8 BANDA ACEH - Khadijah S.Pd (Akademika, 2017)
The main objective of this research is to acquire information on improving textwriting skill of student observation of Grade X, Physics major 5 at SMA Negeri 8 Banda Acehthrough observation of used can drinks. This research applied a classroom action methodwhich was undertaken at SMA Negeri 8 Banda Aceh in 2017. This investigation is carried outon the basis of several stages: planning, classroom action implementation, observation andevaluation. The subject of this research is selected by using a purposive sampling, that is,students of grade X, physics major, SMA Negeri 8 Banda Aceh. the data are collected basedon tests and observation. The data were analyzed by utilizing qualitative analysis. The resultsof research indicated that writing of text observation through observation of used can drinkssucceededinimprovingstudents’writingskillobservation.Theimprovementoccurredintheform of (1) individual students (100%) who reached the scores over 70